Cause and Effect: Testing a Mechanism and Method for the Cognitive Integration of Basic Science. (November 2015) - Kulasegaram, Kulamakan; Manzone, Julian C.; Ku, Cheryl; Skye, Aimee; Wadey, Veronica; Woods, Nicole N.
Abstract : Background: Methods of integrating basic science with clinical knowledge are still debated in medical training. One possibility is increasing the spatial and temporal proximity of clinical content to basic science. An alternative model argues that teaching must purposefully expose relationships between the domains. The authors compared different methods of integrating basic science: causal explanations linking basic science to clinical features, presenting both domains separately but in proximity, and simply presenting clinical features Method: First-year undergraduate health professions students were randomized to four conditions: (1) science–causal explanations (SC), (2) basic science before clinical concepts (BC), (3) clinical concepts before basic science (CB), and (4) clinical features list only (FL). Based on assigned conditions, participants were given explanations for four disorders in neurology or rheumatology followed by a memory quiz and diagnostic test consisting of 12 cases which were repeated after one week. Results: Ninety-four participants completed the study. No difference was found on memory test performance, but on the diagnostic test, a condition by time interaction was found (F[3, 88] = 3.05, P < .03, ηp 2 = 0.10). Although all groups had similar immediate performance, the SC group had a minimal decrease in performance on delayed testing; the CB and FL groups had the greatest decreases. Conclusions: These results suggest that creating proximity between basic science and clinical concepts may not guarantee cognitive integration. Although cause-and-effect explanations may not be possible for all domains, making explicit and specific connections between domains will likely facilitate the benefits of integration for learners.